Fundamental role of local curvature of crystal structure in plastic deformation and fracture of solids; AIP Conference Proceedings; Vol. 1623 : International Conference on Physical Mesomechanics of Multilevel Systems 2014, Tomsk, Russia, 3–5 September 2014 - Panin V. E. Viktor Evgenyevich (2014, 2014)
Title screen